REG-EXPERT: A Knowledge-Based Intelligent Agent for Course Registration - Toprak, İmren (Eastern Mediterranean University EMU, 2015)
In this study, we present the design and implementation of a knowledge-based intelligent software agent for helping advisors and students in the choice of courses during the course registration period every semester in a university setting. The agent has knowledge of university rules and regulations, the curricula in the university, prerequisite information about courses, as well as information about students, including their academic history. Once the courses are selected, the agent then finds an optimal schedule that minimizes the number of clashes during the week by considering different sections of the courses. Keywords: University, Course Registration, Software Intelligent Agent, Knowledge-Based.

ÖZ : Bir üniversite ortamında, her yarı yıl başında ders kayıt dönemi sürecinde ders seçme konusunda danışmanlara ve öğrencilere yardım amaçlı bir uygulama tasarladık. Bu uygulama, bilgi tabanlı akıllı bir yazılım etmenidir. Bu etmen, üniversitenin kuralları ve düzenlemeleri hakkında bilgiye sahiptir. Üniversitenin müfredatı, derslerin önkoşul düzenlemesi bu kurallara örnek verilebilir. Ayrıca, etmenimiz akademik geçmişleri dahil olmak üzere öğrenciler hakkında bilgiye de sahiptir. Dersler seçildikten sonra, akıllı etmen bir derse ait diğer grupları ve aynı dönemde seçilmiş diğer ders gruplarını göz önünde bulundurarak, mümkün olduğunca çakışmasız veya çakışan saat sayısı en düşük seviyede olan ders programını bulmaktadır. Anahtar Kelimeler: Üniversite, Ders Programı, Akıllı yazılım ajanı, Bilgi tabanlı.
Master of Science in Computer Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Computer Engineering, 2015. Supervisor: Assoc. Prof. Dr. Zeki Bayram.
Keywords: Computer Engineering; Intelligent agents (Computer software); Computational intelligence; Expert Systems; University; Course Registration; Software Intelligent Agent; Knowledge-Based